Postnatal corticosteroid treatment as a risk factor for false positivity in severe combined immunodeficiency newborn screening - Po-Sung Chen; Ju Lee; Hui-Ping Pan; Yuh-Jyh Lin; Yung-Chieh Lin; Yu-Shan Chang; Yen-Ju Chen; Chia-Liang Yen; Ching-Wei Lin; Chih-An Chen; Chi-Chang Shieh (Journal of Microbiology, Immunology and Infection, 2023)
From 2011, 37 children were referred to a hospital due to low levels of T cell receptor excision circles (TRECs) from newborn screening. Among them, three children were immunologically characterized and followed up to show that postnatal corticosteroid usage may be among the causes of false positivity in TRECs screening.